ANALISIS PIUTANG USAHA DAN TINGKAT LABA YANG DIHASILKAN PADA PERUSAHAAN PT ASTRA AGRO LESTARI TBK. YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Elviza Elviza; Saska Hayaton Rahmi (STIE DWI SAKTI BATURAJA, 2018)
This research was conducted at PT Astra Agro Lestari Tbk at companies listed on the Stock Exchange in 2015-2017. With the aim of this study to find out and analyze trade accounts receivable and the level of profit and the data used is secondary data. Receivables are one of the main components of working capital, so it is necessary to manage accounts receivable as a result of credit sales. With good accounts receivable management, it is expected that credit sales carried out can increase company profits. From the results of the credit sales carried out, it is expected that income will increase because usually buyers like goods sold on credit, the payment method is lighter, namely the installment system. In addition to these reasons, it is also to find out how much accounts receivable can increase operating profit.